Perancangan User Experience Aplikasi Pendaftaran Rumah Sakit Bhayangkara Surabaya Berbasis Mobile Menggunakan Metode Human-Centered Design (HCD) - Sonia Dwi Suci Hayuningtyas; Buce Trias Hanggara; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Bhayangkara Hospital Surabaya is a service institution in the health sector in Surabaya city under the auspices of Indonesian National Police. Bhayangkara Hospital Surabaya still uses the manual method in its registration administration process which causes long queues. So that Bhayangkara Hospital Surabaya plans to develop a mobile application to make it more easier in its services for users to get health services without going through a long administrative process. The design of this application mobile has an important role, therefore its necessary to have a user experience design to provide application results that comfort when used by users. Human-Centered Design (HCD) is a method used to design user experience of this application mobile, which is used as a reference designing interface of application, focusing on producing useful service systems and focusing on user needs. To find out whether the designed solution is in a accordance with the user's goal, results of the design will be tested using the User Experience Questionnaire (UEQ). The results obtained the mean value of each UEQ scale and showed values in the positive category, namely the good category on the clarity scale, then the excellent category on the efficiency, attractiveness, accuracy, novelty and stimulation scale. So that the Bhayangkara Hospital Surabaya mobile application produces a good user experience design.